Decision Support Model and Software for Consolidated Order Assignment to Delivery Trucks - Leenawong, Chartchai; Wattanawalun, Champ; Wongsa, Kittipish; Lethaisong, Karnkanok (My University, 2017)
In this research, a decision model for assisting in loading consolidated orders onto delivery trucks to distribute to scattered customers is constructed. Each truck can have more than one drop-off location. The case-study company based in Bangkok produces bubble wraps that can simply be stacked up on top of the companys small trucks. Most customer orders are less than truck-load. Thus, consolidating orders into full trucks according to customer locations is necessary to ensure minimum transportation and in-transit inventory carrying costs. 0-1 integer programming is used in the model construction. Also, a decision support system for dealing with this problem is developed for ease of use to logistics managers and planners.
Keywords: 0-1 integer programmer; Decision modeling; Decision support; Distribution